OSL chronostratigraphy of a loess-palaeosol sequence in Saxony/Germany using quartz of different grain sizes - Kreutzer, Sebastian; Fuchs, Markus; Meszner, Sascha; Faust, Dominik (Quaternary geochronology, 2012)
Luminescence dating is one of the leading techniques to establish chronologies for loess-palaeosol sequences and has been successfully applied to different minerals and grain size fractions. Using optical stimulated luminescence (OSL) from quartz, we present for the first time a high resolution chronology for the loess section Ostrau in Saxony/Germany. We compare OSL ages derived from two different grain size fractions, coarse (90-200 μm) and the fine grain (4-11 μm) separates. Our results show that the loess section is divided into two parts, separated by a hiatus. OSL samples from the upper part of the loess section show equivalent doses of De < 100 Gy. De values >180 Gy are observed for the lower part of the loess section. The coarse and fine grain ages agree and also fit to the litho- and pedostratigraphy for the upper part of the profile. For the lower part of the profile the coarse grained quartz OSL is in saturation. The fine grained quartz OSL is not saturated but it appears that the fine grain OSL ages underestimate the sedimentation age. Approaches to explain the De differences between the grain size fractions are presented (e.g. post-depositional translocation, dosimetry). A modified SAR protocol for the fine grain fraction produced ages that are in good agreement with expected ages based on litho- and pedostratigraphy. Although further investigations are needed, our results show the suitability of the Saxonian loess belt for OSL dating.
Online verfügbar: 21. Januar 2012
Gesehen am 31.03.2025